2011
DOI: 10.1073/pnas.1015302108
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical model of ommatidial crystal formation

Abstract: The crystalline photoreceptor lattice in the Drosophila eye is a paradigm for pattern formation during development. During eye development, activation of proneural genes at a moving front adds new columns to a regular lattice of R8 photoreceptors. We present a mathematical model of the governing activator-inhibitor system, which indicates that the dynamics of positive induction play a central role in the selection of certain cells as R8s. The "switch and template" patterning mechanism we observe is mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 53 publications
5
98
1
Order By: Relevance
“…Therefore, the conditions at the wavefront are expected to have relevant consequences for the final pattern of neuronal differentiation. Although the importance of static boundary conditions at the borders of a pattern-forming tissue have received some theoretical notice (Honda et al, 1990;Collier et al, 1996;Murciano et al, 2002;Meir et al, 2002;Plahte, 2001), moving wavefronts of lateral inhibition have only recently come to attention (Owen, 2002;Plahte and Øyehaug, 2007;Pennington and Lubensky, 2010;O'Dea and King, 2011;Lubensky et al, 2011). These studies show how a neurogenic wavefront can sweep across a field of identical cells and leave behind a pattern of different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conditions at the wavefront are expected to have relevant consequences for the final pattern of neuronal differentiation. Although the importance of static boundary conditions at the borders of a pattern-forming tissue have received some theoretical notice (Honda et al, 1990;Collier et al, 1996;Murciano et al, 2002;Meir et al, 2002;Plahte, 2001), moving wavefronts of lateral inhibition have only recently come to attention (Owen, 2002;Plahte and Øyehaug, 2007;Pennington and Lubensky, 2010;O'Dea and King, 2011;Lubensky et al, 2011). These studies show how a neurogenic wavefront can sweep across a field of identical cells and leave behind a pattern of different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot exclude this possibility, the above results suggest that the fourcomponent model with Notch-mediated lateral inhibition is essentially consistent with proneural wave progression in silico and in vivo and that the wave acceleration phenotype is equivalent to the classical neurogenic phenotype of Notch mutant clones (2). Although nonlinear regulations of Notch signaling were implemented in the previous models (5,6,(17)(18)(19), the equation for N in the four-component model was sufficient to reproduce all of the experimental conditions described above. feedback (Fig.…”
Section: Salt and Pepper Pattern Formation Requires A Higher Notch Acmentioning
confidence: 99%
“…Therefore, many of the theoretical studies regard the mode of Notch action during wave propagation as lateral inhibition. Previous mathematical modeling has revealed essential roles for Notch signaling in the formation of a salt and pepper pattern of photoreceptor neurons (17)(18)(19)(20). Although it was suggested that Dl restricts wave propagation during eye development (17), Notch signaling is also required for undifferentiated cells to acquire a proneural state before the wave progression in Significance Notch-mediated lateral inhibition regulates binary cell fate choice, resulting in salt and pepper patterns during various developmental processes.…”
mentioning
confidence: 99%
“…Such self-regulated progression ensures patterning is occurring in a small moving region, in between non-neurogenic tissue and already patterned tissue. From a theoretical point of view, moving wavefronts of lateral inhibition are receiving increasing attention (Owen, 2002;Plahte and Øyehaug, 2007;Pennington and Lubensky, 2010;Lubensky et al, 2011;O'Dea and King, 2011;O'Dea and King, 2012;Formosa-Jordan et al, 2012;Simakov and Pismen, 2013). The advantage of a moving wavefront versus a neurogenic region surrounded by a fixed boundary remains to be elucidated.…”
Section: Perspectivesmentioning
confidence: 99%